Optimizing the Role of PAI Teachers in Fiqh Learning During a Pandemic at MA Nizhamiyah Ploso (SCHOOLAR: Social and Literature Study in Education, 2023)
Learning strategies in Indonesia have changed from year to year, the most certain factor is the development of science and technology, namely Science and Technology, but apart from that there are several other factors that make learning strategies change and develop. The factor that is currently happening is the Covid-19 Pandemic, which is an international outbreak where this outbreak requires learning strategies, especially in Indonesia, to change from face to face to distance. Therefore, the author has a goal to be achieved, namely to find out (1) the role of a good teacher in implementing fiqh learning strategies in the pandemic era, (2) obstacles in optimizing fiqh learning in the pandemic era, (3) teacher efforts to overcome obstacles in optimizing learning fiqh in the pandemic era at the MA Nizhamiyah Ploso school.